(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
The article details the physicochemical mechanisms of the influence of finely dispersed aggregates on cement stone structure formation processes. Three main effects have been described: filling, nucleation, and putzolan. Their synergistic effect on the formation of a dense and strong microstructure has been shown. Introduction. The effectiveness of using finely dispersed aggregates in cement systems is due to their complex effect on hydration and hardening processes. Their role goes beyond simply diluting cement. Understanding the mechanisms of this influence is key to purposeful design of high-quality concrete compositions.